Examining the Effect of Stakeholder Expectations and Environmental Performance on Environmental Disclosure - Dewi Wulansari; Mahfud Sholihin (The Indonesian Journal of Accounting Research, 2017)
Abstract: This study aims to examine the effect of stakeholder expectations and environmental performance on environmental disclosures. Stakeholder expectation is characterized by the influence exerted by internal, external and intermediary stakeholder on environmental disclosure. Environmental performance is proxied by group-level direct and indirect energy consumption and greenhouse gas emissions. Meanwhile, the environmental disclosure is proxied by a disclosure score of environmental information available on firms' environmental or sustainability reports. The sample comprised of European firms extracted from the FTSEurofirst 300 Index Constituents during 2007-2011. The results suggest that neither stakeholder expectations nor environmental performance is related to or associated with environmental disclosure.Abstrak: Penelitian ini bertujuan untuk menguji pengaruh ekspektasi pemangku kepentingan dan kinerja lingkungan pada pengungkapan lingkungan. Harapan pemangku kepentingan dicirikan oleh pengaruh yang diberikan oleh pemangku kepentingan internal, eksternal dan perantara pada pengungkapan lingkungan. Kinerja lingkungan diproksikan dengan konsumsi energi langsung dan tidak langsung tingkat grup dan emisi gas rumah kaca. Sementara itu, pengungkapan lingkungan diproksi dengan skor pengungkapan informasi lingkungan yang tersedia pada laporan lingkungan atau keberlanjutan perusahaan. Sampel terdiri dari perusahaan-perusahaan Eropa yang diekstraksi dari FTSEurofirst 300 Index Constituents selama 2007-2011. Hasilnya menunjukkan bahwa baik harapan pemangku kepentingan maupun kinerja lingkungan terkait atau terkait dengan pengungkapan lingkungan.